A new perspective on cerebrospinal fluid dynamics after subarachnoid hemorrhage: From normal physiology to pathophysiological changes. Issue 4 (April 2022) - Fang, Yuanjian; Huang, Lei; Wang, Xiaoyu; Si, Xiaoli; Lenahan, Cameron; Shi, Hui; Shao, Anwen; Tang, Jiping; Chen, Sheng; Zhang, Jianmin; Zhang, John H
Knowledge about the dynamic metabolism and function of cerebrospinal fluid (CSF) physiology has rapidly progressed in recent decades. It has traditionally been suggested that CSF is produced by the choroid plexus and drains to the arachnoid villi. However, recent findings have revealed that the brain parenchyma produces a large portion of CSF and drains through the perivascular glymphatic system and meningeal lymphatic vessels into the blood. The primary function of CSF is not limited to maintaining physiological CNS homeostasis but also participates in clearing waste products resulting from neurodegenerative diseases and acute brain injury. Aneurysmal subarachnoid hemorrhage (SAH), a disastrous subtype of acute brain injury, is associated with high mortality and morbidity. Post-SAH complications contribute to the poor outcomes associated with SAH. Recently, abnormal CSF flow was suggested to play an essential role in the post-SAH pathophysiological changes, such as increased intracerebral pressure, brain edema formation, hydrocephalus, and delayed blood clearance. An in-depth understanding of CSF dynamics in post-SAH events would shed light on potential development of SAH treatment options. This review summarizes and updates the latest physiological characteristics of CSF dynamics and discusses potential pathophysiological changes and therapeutic targets after SAH.